2013
DOI: 10.1093/bjsw/bct033
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Assessing Substance Use: Findings from a National Survey of Social Work and Social Care Professionals

Abstract: Social care practitioners regularly encounter problematic substance use among their service users. However, most social care practitioners do not specialise in substance use and there is limited evidence on their practice with it. Aims: This study aimed to explore the practice of social care professionals when they encounter substance use in the course of their work. This article focuses specifically on how they identify and assess substance use. Method: A web-based survey was disseminated to 3164 practitioner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…In children and families social work, concerns about parental misuse of drugs or alcohol are associated with poor outcomes for children [8], and the issues arising can be complex [9]. Assessment of parental substance use by social care professionals has been found to take place ‘often at a late stage with little to no guidance on how to do so effectively’ (p. 1) [10]. One randomised trial involving training for child‐care social workers showed that this was challenging [11].…”
Section: Introductionmentioning
confidence: 99%
“…In children and families social work, concerns about parental misuse of drugs or alcohol are associated with poor outcomes for children [8], and the issues arising can be complex [9]. Assessment of parental substance use by social care professionals has been found to take place ‘often at a late stage with little to no guidance on how to do so effectively’ (p. 1) [10]. One randomised trial involving training for child‐care social workers showed that this was challenging [11].…”
Section: Introductionmentioning
confidence: 99%
“…Having one parent without an alcohol problem in a household can offer some protection against adverse outcomes . However, children who live with two heavily drinking parents, and those living with lone parents with alcohol problems, are of significant concern . A further particularly vulnerable group are ‘looked‐after children’ who experience foster or state‐provided residential care .…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Social workers report a sense of role legitimacy in asking parents about alcohol use, but also difficulty in identifying alcohol problems . This puzzling situation occurs because informal self‐assessment approaches are used typically, which may lead to under‐reporting of problems . Moreover, parents often do not receive alcohol intervention, as practitioners often place more focus on illicit drug use.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…The motivational work inherent within some forms of brief intervention may offer an opportunity to work with the seemingly ubiquitous resistance found within child and families social work (Forrester et al, 2012). However, as the vast majority of social work contacts occur in non-substance specialist services, social workers often report difficulties in this role (Galvani et al, 2013) and a lack of knowledge on how to intervene to promote change (Galvani and Hughes, 2010). Brief interventions are designed to be delivered opportunistically, at the point of contact with non-substance specialists.…”
Section: Commentmentioning
confidence: 99%